2019
DOI: 10.1002/jsfa.10007
|View full text |Cite
|
Sign up to set email alerts
|

Preharvest application of methyl jasmonate increases crop yield, fruit quality and bioactive compounds in pomegranate ‘Mollar de Elche’ at harvest and during postharvest storage

Abstract: BACKGROUND: Previous reports have addressed the effectiveness of postharvest methyl jasmonate (MeJA) treatments on maintaining quality properties of pomegranate fruit during storage. However, there is no literature regarding the effects of preharvest MeJA treatments on pomegranate 'Mollar de Elche' crop yield, fruit ripening, quality attributes and bioactive compounds content (at harvest or after long-term storage), which were evaluated in this research. RESULTS: PreharvestMeJA treatments (1, 5, and 10 mmol L … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 45 publications
5
56
0
7
Order By: Relevance
“…This sugar profile is in agreement with previous reports on ‘Mollar de Elche’ and other sweet pomegranate cultivars, while in sour cultivars the major organic acid is citric acid ( Nuncio-Jáuregui et al, 2014 ; Cano-Lamadrid et al, 2018 ). In addition, increases in weight losses ( Supplementary Figure S1 ) and decreases in firmness ( Supplementary Figure S2A ) and arils Hue angle ( Supplementary Figure S2B ) show the normal evolution of the postharvest ripening process in “Mollar de Elche” and other pomegranate cultivars ( Sayyari et al, 2011a , 2016 ; García-Pastor et al, 2020 ), which were delayed by pre-harvest salicylate treatments. Accordingly, the evolution of the postharvest ripening process was delayed in two sweet cherry cultivars by pre-harvest treatments with SA, ASA, and MeSa leading to maintenance of fruit quality parameters ( Valverde et al, 2015 ; Giménez et al, 2017 ).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This sugar profile is in agreement with previous reports on ‘Mollar de Elche’ and other sweet pomegranate cultivars, while in sour cultivars the major organic acid is citric acid ( Nuncio-Jáuregui et al, 2014 ; Cano-Lamadrid et al, 2018 ). In addition, increases in weight losses ( Supplementary Figure S1 ) and decreases in firmness ( Supplementary Figure S2A ) and arils Hue angle ( Supplementary Figure S2B ) show the normal evolution of the postharvest ripening process in “Mollar de Elche” and other pomegranate cultivars ( Sayyari et al, 2011a , 2016 ; García-Pastor et al, 2020 ), which were delayed by pre-harvest salicylate treatments. Accordingly, the evolution of the postharvest ripening process was delayed in two sweet cherry cultivars by pre-harvest treatments with SA, ASA, and MeSa leading to maintenance of fruit quality parameters ( Valverde et al, 2015 ; Giménez et al, 2017 ).…”
Section: Discussionmentioning
confidence: 94%
“…Control trees were sprayed with distilled water containing 1 mL L –1 Tween-20. Dates of treatments were set by taking into account the harvest dates of this cultivar in similar growing conditions in previous seasons, so that the first treatment was applied before the skin color changes and the last one 4 days before the first harvest, according to previous reports ( García-Pastor et al, 2020 ). Dates of treatments in 2017 were: 3rd July, 2nd August, 1st September, and 2nd October.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Jasmonates (JAs) have been identified as hormones that participate in many physiological processes, including fruit ripening and pigment accumulation. 15 Many previous studies have reported that JAs and its derivatives can promote anthocyanin accumulation in different fruits such as strawberry, 16 grape, 17 pomegranate, 18 peach, 19 blueberry, 20 and mango. 11 In purple mustard, MeJA can promote anthocyanin accumulation and stimulate the expression of genes encoding components of the MBW complex (MYB, bHLH, and WD40).…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous supply of MeJA to an ornamental plant Malus crabapple (Rosaceae) was protective to ozone stress-induced toxicity [ 39 ] or reduced effect of cadium-induced injury in rice seedlings [ 40 ]. It has also been reported that MeJA treatment increased postharvest chilling tolerance in fruits of tomato ( Lycopersicon esculentum ) [ 41 ], avocados ( Persea americana ) [ 42 ], blood orange ( Citrus sinensis ) [ 43 ] and pomegranate ( Punica granatum ) [ 44 ]. Exogenous MeJA improved salt tolerance in almond ( Prunus dulcis ) [ 45 ] and sea-lavender ( Limonium bicolor ) [ 46 ].…”
Section: Introductionmentioning
confidence: 99%